Acoustic-phonetic variability of Polish vowels - JASSEM, W. (Archives of Acoustics, 1992)
Since the early 1960’s speech sounds have been described at three levels of abstraction: intrinsic-allophonic, extrinsic-allophonic and phonemic. The acoustic features of Polish vowels have been investigated at the first and the last of these levels by acoustic-phonetic personally techniques, but extrinsic allophony has so far been largely ignored. Phonemic distinctions have been investigated in terms of format frequencies and it has been found that F_1 and F_2 are sufficient to distinguish between all the 7 Polish vowel phonems. They are also distinctive, though less strongly both in isolation and in running speech. In the latter case the formant frequencies vary with time even within a single vocalic segment, but advanced statistical methods permit their identification on the basis of trajectories in an F_1-F_2 plane. There are interactions between segmental and suprasegmental factors. Thus, speech tempo affects the formant trajectories. Otherwise, such interactions have not been extensively studied and one of the open problems is the effect of F0 on the vowel formants. Studies of the relations between vowel-formant frequencies and speaker gender and age have, in the case of Polish speech, only just been started.